Strategic Capacity Management for Competitive Advantage: A Systematic Literature Review of Operational, Technological, and Sustainability Perspectives - Masduki Asbari; Dewiana Novitasari; Firdaus Putra (Yayasan Aya Sophia Indonesia, 2026)
Capacity management has become a critical strategic imperative for global organisations in the face of uncertain and complex market dynamics. This comprehensive literature review analyses 11 reputable Scopus Q1 articles (2021–2026) addressing capacity management within the contexts of supply chains, manufacturing, tourism, and business systems. This study identifies five key dimensions: (1) volume flexibility and capacity management, (2) supply chain capacity management and resilience, (3) destination capacity, (4) production planning and manufacturing capacity, and (5) business process optimisation. The analysis reveals a significant shift from a purely tactical-operational approach towards a holistic perspective that integrates strategic, technological, and sustainability dimensions. Empirical findings indicate that companies optimising production capacity utilisation achieve 15–30% higher operational efficiency than their competitors, with average global capacity utilisation reaching only 70–80% across all industrial sectors. This research synthesises three main theoretical frameworks—the Resource-Based View (RBV), the Dynamic Capability View (DCV), and the Technology-Organisation-Environment (TOE) framework—to develop a comprehensive understanding of capacity management as a driver of competitive advantage. Innovative contributions include: (1) a systematic mapping of the contemporary capacity management research landscape that identifies emerging trends and the evolution of intellectual discourse; (2) a holistic integration of operational, strategic, technological, and sustainability perspectives previously fragmented across the literature; and (3) the identification of critical research gaps and future research directions that guide academic inquiry and industrial practice. Research impact: This literature review bridges a significant knowledge-practice gap in the implementation of capacity management, particularly for SMEs and emerging markets, and provides a practical framework for integrating AI, IoT, and cloud computing technologies into capacity decision-making systems.